(untitled) (Mustansiria Dental Journal, 2024)
Background: The import of the rough surface makes the application of several elements to enhance this feature vital for the adhesion of soft liners. Aim: The study’s goal was to to ascertain the impact of copper oxide nanoparticles added in two ratios to heated-cured acrylic resin and fiber laser surface treatment on surface roughness. Materials and methods:60 acrylic specimens in the shape of discs were manufactured and divided into three groups: one received no addition; the other two received the addition of 0.3% CuO NPs; and a third group that received the addition of 0.5% CuO NPs. Each group was divided into two categories: those that were laser treatment and those who did not. The surface roughness test was then examined using a roughness tester called a profilometer. Results: The average roughness values were high for the control groups and low for the CuO NPs 0.5% groups. The mean values in the laser-treated groups had greater roughness than the control groups, according to the laser application.Conclusion:. As the fraction of CuO NPs increased, the surface roughness reduced. The laser treatment also reduced surface roughness.